Gender differences in biochemical markers and oxidative stress of rats after 28 days oral exposure to a mixture used for weight loss containing p-synephrine, ephedrine, salicin, and caffeine (Brazilian Journal of Pharmaceutical Sciences, 2016)
The association of p-synephrine, ephedrine, salicin, and caffeine in dietary supplements and weight loss products is very common worldwide, even though ephedrine has been prohibited in many countries. The aim of this study was to evaluate a 28-day oral exposure toxicity profile of p-synephrine, ephedrine, salicin, and caffeine mixture (10:4:6:80 w/w respectively) in male and female Wistar rats. Body weight and signs of toxicity, morbidity, and mortality were observed daily. After 28 days, animals were euthanized and blood collected for hematological, biochemical, and oxidative stress evaluation. No clinical signs of toxicity, significant weight loss or deaths occurred, nor were there any significant alterations in hematological parameters. Biochemical and oxidative stress biomarkers showed lipid peroxidation, and hepatic and renal damage (p < 0.05; ANOVA/Bonferroni) in male rats (100 and 150 mg/kg) and a reduction (p < 0.05; ANOVA/Bonferroni) in glutathione (GSH) levels in all male groups. Female groups displayed no indications of oxidative stress or biochemical alterations. The different toxicity profile displayed by male and female rats suggests a hormonal influence on mixture effects. Results demonstrated that the tested mixture can alter oxidative status and promote renal and hepatic damages.